Original articleComparison of two techniques of interstitial pulsed dose rate boost brachytherapy in conservative treatment of breast cancer - Serkies, Krystyna; Tarnawska, Zofia; Blukis, Andrzej; Badzio, Andrzej; Jaśkiewicz, Janusz; Jassem, Jacek (Journal of Contemporary Brachytherapy, 2009)
Purpose: The aim of this work is to compare selected parameters of implants and natural dose volume histograms for two techniques of interstitial pulsed dose rate brachytherapy (PDR BT) as a boost to the tumour bed in breast-conserving therapy (BCT). Material and methods: Data of T1-3N0-2M0 breast cancer patients who underwent BCT with BT boost between 05.2002 and 12.2008 were analysed. Ninety two patients were implanted with rigid tubes after breast irradiation (group A) and 96 had a peri-operative BT with an intra-operative flexible tube placement and subsequent whole breast radiotherapy (group B). In both groups PDR BT of 15 Gy (1 Gy/pulse/h) was administered based on Paris system rules, and volume optimization using BT planning system PLATO. Results: Three-plane implant was used in 62% and 8% of patients in group A and B, respectively, and two-plane implant in 38% of group A and in 84% of group B, with a median of 11 and 9 tubes respectively. The average volume for the prescribed dose (V100) was 42.0 ± 25.4 cc (group A) and 34.1 ± 19.7 cc (group B), respectively (p = 0.017). The individual V50 and V200 were similar. Quality index (QI) was not impacted by the technique of BT (mean QI was 1.80 ± 0.10 and 1.75 ± 0.46 for the groups A and B, respectively). Uniformity index (UI) in respective groups was 1.60 ± 0.10 and 1.52 ± 0.21 (p = 0.001). Conclusions: Implant volume encompassed by prescribed dose was significantly lower with intra-operative plastic tubes placement. In respect to the QI, these two BT techniques were comparable. The target volume coverage by the dose distribution as defined by UI was better for rigid tubes.